Country-level gender inequality is associated with structural differences in the brains of women and men - Zugman, André; Alliende, Luz María; Medel, Vicente; Bethlehem, Richard A I; Seidlitz, Jakob; Ringlein, Grace; Arango, Celso; Arnatkevičiūtė, Aurina; Asmal, Laila; Bellgrove, Mark; Benegal, Vivek; Bernardo, Miquel; et al. (Proceedings of the National Academy of Sciences - PNAS, 2023)
Gender inequality across the world has been associated with a higher risk to mental health problems and lower academic achievement in women compared to men. We also know that the brain is shaped by nurturing and adverse socio-environmental experiences. Therefore, unequal exposure to harsher conditions for women compared to men in gender-unequal countries might be reflected in differences in their brain structure, and this could be the neural mechanism partly explaining women's worse outcomes in gender-unequal countries. We examined this through a random-effects meta-analysis on cortical thickness and surface area differences between adult healthy men and women, including a meta-regression in which country-level gender inequality acted as an explanatory variable for the observed differences. A total of 139 samples from 29 different countries, totaling 7,876 MRI scans, were included. Thickness of the right hemisphere, and particularly the right caudal anterior cingulate, right medial orbitofrontal, and left lateral occipital cortex, presented no differences or even thicker regional cortices in women compared to men in gender-equal countries, reversing to thinner cortices in countries with greater gender inequality. These results point to the potentially hazardous effect of gender inequality on women's brains and provide initial evidence for neuroscience-informed policies for gender equality.